"Planificación estratégica y cuadro de mando integral para el observatorio de comercio exterior e inversión extranjera. Universidad de Otavalo - Feijoó, Erik J. (2019)
This paper presents a proposal for strategic planning with a comprehensive scorecard for the Observatory of Foreign Trade and Foreign Investment of the University of Otavalo. In Chapter I, we talk about the theoretical foundations of the subject analyzed considering the concepts of strategic planning and their importance within companies and organizations, as well as the parameters to be considered in the comprehensive scorecard (CMI) Chapter II reflects that the Observatory of Foreign Trade and Foreign Investment is a project in process of formation within the University in this chapter establishes the methodology to be developed and the instruments used in the investigation, as well as the weights to Use in research. Chapter III presents the proposal for strategic planning for the (OCEIE), considering as its main purpose the design of a strategic address and the management control system, as well as the determination of strategic maps and dashboards To strengthen the management of the observatory and thus propose the foundations of a functional control board that allows monitoring the results achieved periodically, it also establishes the mission, vision, policies, values, objectives and goals that represent the basis for the development, implementation and evaluation of key strategies that the OCEIE will require to face different adverse situations and adapt to successful changes. In addition, the conclusions and recommendations that are made based on the study of strategic planning for the (OCEIE) of the University of Otavalo are presented in order to use the recommendations in the execution of the project and the application of the strategic model proposed.